2016
DOI: 10.1007/s11605-015-3060-4
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Does Not Impact Perioperative or Postoperative Outcomes in Patients with Inflammatory Bowel Disease

Abstract: Obesity does not appear to impact intraoperative variables nor does obesity appear to worsen postoperative complication rates in IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…Although some studies have not found obesity to influence all of these complications, the association of obesity with prolonged operative time has consistently been recognized . Obesity reportedly does not influence intraoperative variables or postoperative complications in patients with inflammatory bowel diseases, such as Crohn's disease and ulcerative colitis, undergoing gastrointestinal surgical resection …”
Section: Colorectal Surgerymentioning
confidence: 99%
“…Although some studies have not found obesity to influence all of these complications, the association of obesity with prolonged operative time has consistently been recognized . Obesity reportedly does not influence intraoperative variables or postoperative complications in patients with inflammatory bowel diseases, such as Crohn's disease and ulcerative colitis, undergoing gastrointestinal surgical resection …”
Section: Colorectal Surgerymentioning
confidence: 99%
“…Several studies have shown association of obesity with increased operative times, increased blood loss, and a higher risk of conversion from laparoscopic to open surgeries 20,21 . In contrast to this, a retrospective cohort study including 391 IBD patients undergoing surgery found that 30-day postoperative complication rates including total complications, wound infection, or anastomotic leak did not vary according to BMI 22 . The inconsistency of these studies may because that they did not evaluate further into visceral obesity, which is a more representative parameter of body fat.…”
Section: Discussionmentioning
confidence: 62%
“…Male gender and higher BMI were identified as independent risk factors for PRC. Guardado et al [10] reported that higher BMI (≥30) did not appear to affect intraoperative variables such as estimated blood loss and mean operative time; BMI also did not appear to worsen postoperative complications in UC and CD patients. Krane et al [13] reported that higher BMI (≥25) increased the amount of hemorrhaging and the operative duration but made no difference in postoperative outcomes in IBD patients, including patients with UC and CD.…”
Section: Discussionmentioning
confidence: 94%
“…However, data on the influence of higher BMI on perioperative outcomes in patients with IBD are sparse and controversial. Higher BMI increased the risk of postoperative complications following restorative proctocolectomy with an ileal pouch-anal anastomosis (IPAA), but higher BMI did not appear to impact intraoperative variables; also, higher BMI did not appear to worsen postoperative complication rates in UC and CD patients [9,10].…”
Section: Introductionmentioning
confidence: 99%